Hubungan Tingkat Pengetahuan dengan Kecemasan Remaja dalam Menghadapi Menarche pada Remaja Usia 10-13 Tahun di Desa Talawaan - Wuisan, Maria; Natalia, Adriani; Gannika, Lenny (Mapalus Nursing Science Journal, 2025)
Background: Knowledge is the result of "knowing" and this occurs after people perceive a particular object, anxiety is a subjective feeling of disturbing mental tension as a general reaction to the inability to solve a problem or a lack of security. Research Objectives: To determine the relationship between the level of knowledge and the anxiety level of adolescents in facing menarche in grades V and VI at St Nikolaus Catholic Elementary School, SD N 1, SD N 2, SD GP Talawaan. Research Methods: This research was conducted on students of grades V & VI SD with a total sample of 84 students. The sampling technique uses a purposive sample. Research Results: The results in this study were that the majority of respondents had a good level of knowledge as many as 78 people (92.2%). The majority of respondents experienced mild anxiety as many as 59 people (70.2%). Conclusion: There is no relationship between the level of knowledge and the level of adolescent anxiety in facing menarche in grades V and VI at St Nikolaus Catholic Elementary School, SD N 1, SD N 2, SD GP Talawaan. Suggestion: This research is expected to be a guideline for existing teachers to maintain education about menarche in grades V & VI SD.